Elderly patients and the idea of having medication deprescribed: a mixed method study in Portuguese primary health care - Simões, Pedro Augusto Gomes Rodrigues Marques (2021)
Introduction Deprescribing is the process of tapering or stopping medications aiming at improving patient outcomes and optimising current therapy. Some studies tried to identify which patients will have inappropriate medication deprescribed, but none found any association with sociodemographic and clinical characteristics, number of prescribed medications or time length. Our aim was to determine Portuguese elderly patients’ attitudes and beliefs regarding medication use and their willingness to have regular medications deprescribed. Material and methods We conducted a cross-sectional study in triangulation in primary care centres from mainland Portugal and its autonomous regions. We used a random sample of 386 polymedicated older adult patients that answered the questionnaire between October 2018 and February 2019. For the quantitative analysis, we used sociodemographic characteristics, clinical profile and medication. For the qualitative analysis, we studied an included open-question by coding participants’ answers, common codes were grouped together. Convergent mixed methods design was performed. Results 74.0% expressed the belief that medicines were generally beneficial. 19.9% reported a strong belief that medicines were harmful and 33.4% that they were overused. 61.8% were against the idea of deprescribing and 24.6% were in favour of deprescription. Those against the idea had lower education level (p=0.006) and a higher number of self-perceived morbidities (p=0.001) than those not against it. Conclusions Medication benefits were accepted by the majority of patients who also were against the idea of deprescribing. It is important that doctors are aware of this reality, namely in the primary care setting. Addressing the patients’ fears and beliefs and making the deprescribing process possible.